Elucidation of Zero‐Dimensional to Two‐Dimensional Growth Transition in MoS2 Chemical Vapor Deposition Synthesis. Issue 4 (24th October 2016) - Liang, Tao; Xie, Shuang; Huang, Zhuoting; Fu, Weifei; Cai, Yu; Yang, Xi; Chen, Hongzheng; Ma, Xiangyang; Iwai, Hideo; Fujita, Daisuke; Hanagata, Nobutaka; Xu, Mingsheng
Abstract : The 0D–2D nucleation and growth mode is presented in molybdenum disulfide (MoS2 ) chemical vapor deposition synthesis. Partially sulfured molybdenum suboxide nucleation centers are demonstrated experimentally, followed by these centers being converted to MoS2 nanoparticles and MoS2 layer growth initiation from the nanoparticle edges. The work reveals the mechanism for MoS2 nucleation and growth.